Targeted Interleukin‐9 delivery in pulmonary hypertension: Comparison of immunocytokine formats and effector cell study. (26th November 2022) - Heiss, Judith; Grün, Katja; Tempel, Laura; Matasci, Mattia; Schrepper, Andrea; Schwarzer, Michael; Bauer, Reinhard; Förster, Martin; Berndt, Alexander; Jung, Christian; Schulze, P. Christian; Neri, Dario; et al.
Abstract: Aims: Pulmonary hypertension (PH) is accompanied by pulmonary vascular remodelling. By targeted delivery of Interleukin‐9 (IL9) via the immunocytokine F8IL9, beneficial effects could be demonstrated in a mouse model of PH. This study aimed to compare two immunocytokine formats (single‐chain Fv and full IgG) and to identify potential target cells of IL9. Methods: The Monocrotaline mouse model of PH (PH, n = 12) was chosen to evaluate the treatment effects of F8IL9F8 ( n = 12) and F8IgGIL9 ( n = 6) compared with sham‐induced animals (control, n = 10), the dual endothelin receptor antagonist Macitentan (MAC, n = 12) or IL9‐based immunocytokines with irrelevant antigen specificity (KSFIL9KSF, n = 12; KSFIgGIL9 n = 6). Besides comparative validation of treatment effects, the study was focused on the detection and quantification of mast cells (MCs) and regulatory T cells (Tregs). Results: There was a significantly elevated systolic right ventricular pressure (104 ± 36 vs. 45 ± 17 mmHg) and an impairment of right ventricular echocardiographic parameters (RVbasal: 2.52 ± 0.25 vs. 1.94 ± 0.13 mm) in untreated PH compared with controls ( p < 0.05). Only the groups treated with F8IL9, irrespective of the format, showed consistent beneficial effects ( p < 0.05). Moreover, F8IL9F8 but not F8IgGIL9 treatment significantly reduced lung tissue damage compared with untreated PH mice ( p < 0.05). There was a significant increase in Tregs in F8IL9‐treated compared with control animals, the untreated PH and the MAC group ( p < 0.05). Conclusions: Beneficial treatment effects of targeted IL9 delivery in a preclinical model of PH could be convincingly validated. IL9‐mediated recruitment of Tregs into lung tissue might play a crucial role in the induction of anti‐inflammatory and anti‐proliferative mechanisms potentially contributing to a novel disease‐modifying concept. Abstract : Administration of the immunocytocine F8IL9 in mice induced with pulmonary hypertension enables a targeted transfer of IL9 into the inflamed lung tissue. Beneficial effects on PH severity were associated with a recruitment of regulatory T cells into the lung.